The Pengaruh latihan circuit weight training terhadap kekuatan otot lengan siswa ekstrakurikuler bolavoli di SMPN 42 Jakarta - Islami, Haydar; Lasma, Yunita; Mamesah, Elly Diana (Motion: Journal Research of Physical Education, 2025)
The purpose of this study was to determine whether circuit weight training can increase arm muscle strength in extracurricular bolavoli students at SMPN 42 Jakarta. The research method used in this research is to use the experimental method. This research was conducted at SMPN 42 Jakarta, while the population of this study were extracurricular bolavoli students of SMPN 42 Jakarta, totaling 40 people. For sampling techniques and the number of samples used purposive sampling techniques totaling 20 people. For data analysis the authors used normality, homogeneity and significance t tests. Based on the results of the study, it is known that the significance value of the initial and final tests is 0.000, this value is smaller than 0.05. The conclusion of this study is that there is a significant effect of circuit weight training on arm muscle strength in volley ball extracurricular students at SMPN 42 Jakarta